Aesthetic film: constructive perspective art directors - Salsa Solli Nafsika; Zakarias Sukarya Soeteja; Irwan Sarbeni; Hery Supiarza (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The audience has limited information when it comes to interpreting movies, and they can even be swayed by an artistic director's failure to create a scene event space, which affects how visual messages are conveyed. This study analyzes the aesthetics of the film using an art directors practice approach to: measure the extent of the relationship between the perceptions built by the film appreciator and the visual objects he observes through Persistence of Vision, revealing the relevance of object and artistic form to mise-en-scene; and the illusion of depth and semiosis. This study uses qualitative methods and research data processing by triangulation method and content analysis. The study's findings indicate that additional disciplines, such as aesthetic philosophy, semiotics, perspective, visual communication, mise-en-scene, and art director work practices, are needed to analyse cinema aesthetics from an art director's point of view